Using extracellular matrix derived from sugen-chronic hypoxia lung tissue to study pulmonary arterial hypertension - Link, Patrick A.; Farkas, Laszlo; Heise, Rebecca L. (Frontiers in Pharmacology, 2023)
Pulmonary arterial hypertension has characteristic changes to the mechanical environment, extracellular matrix, and cellular proliferation. In order to develop a culture system to investigate extracellular matrix (ECM) compositional-dependent changes in pulmonary arterial hypertension, we decellularized and characterized protein and lipid profiles from healthy and Sugen-Chronic Hypoxia rat lungs. Significant changes in lipid profiles were observed in intact Sugen-Hypoxia lungs compared with healthy controls. Decellularized lung matrix retained lipids in measurable quantities in both healthy and Sugen-Chronic Hypoxia samples. Proteomics revealed significantly changed proteins associated with pulmonary arterial hypertension in the decellularized Sugen-Chronic Hypoxia lung ECM. We then investigated the potential role of healthy vs Sugen-Chronic Hypoxia ECM with controlled substrate stiffness to determine if the ECM composition regulated endothelial cell morphology and phenotype. CD117+ rat lung endothelial cell clones were plated on the gels and cellular proliferation, morphology, and gene expression were quantified. Sugen-Chronic Hypoxia ECM on healthy stiffness gels produced significant changes in cellular gene expression levels of Bmp2, Col1α1, Col3α1 and Fn1. The signaling and cell morphology observed at low substrate stiffness suggests early changes to the ECM composition can initiate processes associated with disease progression. These data suggest that Sugen-Chronic Hypoxia ECM can be used to investigate cell-ECM interactions relevant to pulmonary arterial hypertension.